Novel BQCA‐ and TBPB‐Derived M1 Receptor Hybrid Ligands: Orthosteric Carbachol Differentially Regulates Partial Agonism. (3rd July 2019) - Schramm, Simon; Agnetta, Luca; Bermudez, Marcel; Gerwe, Hubert; Irmen, Matthias; Holze, Janine; Littmann, Timo; Wolber, Gerhard; Tränkle, Christian; Decker, Michael
Abstract: Recently, investigations of the complex mechanisms of allostery have led to a deeper understanding of G protein‐coupled receptor (GPCR) activation and signaling processes. In this context, muscarinic acetylcholine receptors (mAChRs) are highly relevant due to their exemplary role in the study of allosteric modulation. In this work, we compare and discuss two sets of putatively dualsteric ligands, which were designed to connect carbachol to different types of allosteric ligands. We chose derivatives of TBPB [1‐(1′‐(2‐tolyl)‐1, 4′‐bipiperidin‐4‐yl)‐1 H ‐benzo[ d ]imidazol‐2(3 H )‐one] as M1 ‐selective putative bitopic ligands, and derivatives of benzyl quinolone carboxylic acid (BQCA) as an M1 positive allosteric modulator, varying the distance between the allosteric and orthosteric building blocks. Luciferase protein complementation assays demonstrated that linker length must be carefully chosen to yield either agonist or antagonist behavior. These findings may help to design biased signaling and/or different extents of efficacy. Abstract : Tailor made : Dualsteric compounds derived from carbachol as orthosteric moiety can be tailored to activate or inactivate the muscarinic M1 acetylcholine receptor to various extents. Carbachol‐appended derivatives of BQCA and TBPB show partial agonism or a formally competitive antagonism with orthosteric carbachol, respectively, and the degree of intrinsic receptor response can be controlled in a wide range.